GROSS REGIONAL DOMESTIC PRODUCT FORECASTS USING TREND ANALYSIS: CASE STUDY OF BANGKA BELITUNG PROVINCE - Oktaviana, Nurmalita; Amalia, Nurisqi (Universitas Muhammadiyah Yogyakarta, 2018)
Gross Regional Domestic Product (GRDP) is one of the important indicators to determine the economic conditions in the region. This study aims toÂ forecastÂ the Gross Regional Domestic Product (GRDP) of the Province of Bangka Belitung Islands which is dominated by tourism sector. This forecasting to be expected to give information to formulate a type of policy action that will be conducted by decision makers based on GRDP data. GRDP data are from the first quarter of 2010 to the fourth quarter of 2017 on the basis of constant prices in 2010. Data sources are obtained from Central Bureau of Statistics (BPS) of the Province of Bangka Belitung Islands. The forecasting method used is the research is trend analysis. The results of the GRDP forecasting of Bangka Belitung Province in the first quarter of 2018 to the fourth quarter of 2022 shows an increasing trend. It can be seen from historical data that shows an increasing trend as evidenced from the graph on linear trends. The increasing trend in GRDP of the Bangka Belitung Islands Province for the next five years is supported by government policies that prioritize the tourism sector. Consequently, by prioritizing the tourism sector, this will increase economic growth and can reduce GRDP dependency on mining sector, especially tin that has been continuously decreased.